Diet-derived nutrient patterns and components of metabolic syndrome: a cross-sectional community- based study - Vajdi, Mahdi; Farhangi, Mahdieh Abbasalizad; Nikniaz, Leila (BMC endocrine disorders, 2020)
Background Metabolic syndrome (MetS) is one of the main public health problems worldwide. Although some relations between dietary intakes and MetS have been found, few studies have focused on association between dietary nutrients interactions and the risk of the MetS and its components. The aim of the present study was to examine the association between nutrient patterns and MetS and its components among Iranian adult population. Methods A total of 588 subjects (aged 18–64 years, 271 males and 317 females) enrolled in the cross sectional study. Dietary consumption was evaluated using an 80-item food frequency questionnaire (FFQ). Biochemical assessments including fasting blood sugar (FBS), aspartate aminotransferase (AST), alanine amino transferase (ALT) and serum lipids were performed by enzymatic methods. Nutrient patterns were obtained by factor analysis procedure using principal component method. Multinational logistic regression analysis was used to evaluate the association between nutrient patterns and MetS and its components. Results Three nutrient patterns explaining 53.66% of the variance in dietary nutrients intake, were recognized in the current study. Animal-sourced nutrient pattern was significantly associated with the higher odds of MetS and high triglyceride (TG) levels. Plant-sourced nutrient pattern (high intake of fiber, carbohydrate, vitamins B 6 , B 3 , C, B 1 , E, D, magnesium, potassium, and linoleic acid) was significantly associated with lower risk of MetS and lower blood pressure ( p < 0.05). Third nutrient pattern (mixed-source) was significantly related to higher risk of MetS, high waist circumference (WC) and high systolic blood pressure (SBP). Conclusion This present study confirms the important effect of nutrients and their patterns on MetS risk. Our results suggest that adherence to the nutrient pattern rich in fiber, carbohydrate, vitamins D, B 6 , B 3 , C, B 1 , E, magnesium, potassium, linoleic acid, and docosahexaenoic acid (DHA) is associated with a lower risk of MetS, while animal- and mixed-sourced nutrient patterns are positively associated with greater odds of MetS; However, further longitudinal and interventional studies are required to make a clear conclusion.